Effect of Principal’s Coaching and Supervision toward Teacher’s Performance - Nurma Atiah; Happy Fitria; Destiniar Destiniar (Universitas Bengkulu, 2021)
This study determined the effect of the pattern of guidance and supervision of school’s principals on teacher’s performance in SD Negeri 1 Gardu Harapan, Lais, Musi Banyuasin both persially and jointly. The instrument used was a questionnaire. Data analysis techniques use statistics. The results of this study obtained that the pattern of guidance and supervision of the Principal significantly influence the performance of teachers of SD Negeri 1 Gardu Harapan. This research contributes that if you want to improve teacher performance, you have to improve the pattern of coaching and supervision.